(untitled) (Homoeopathy for All, 2023)
Eczema is a prevalent skin condition that is long-lasting, not contagious, and is characterized by dry skin, red scaly patches in one area, intense itchiness, and skin discomfort. This the skin becomes less capable of retaining moisture and safeguarding against bacteria, irritants, allergens, and environmental factors such as tobacco smoke. Other causes include the excessive presence of Staphylococcus aureus bacteria on the skin.3condition can also be referred to as atopic eczema, neurodermatitis, or atopic dermatitis.1 It affects proportion of 20% children’s and 10% adults’ population in India and ranks as the 15th most common non-fatal disease worldwide and is the leading skin disease in terms of disability-adjusted life years (DALYs). The skin eruptions linked with eczema are recognizable due to the presence of small raised bumps, formation of crusts and scales, fluid-filled blisters on reddened and swollen skin. Though, in darker skin, it might be tough to recognize the redness. When the eruptions or scales persist for long periods, the skin might thicken resulting in a condition called lichenification.2